2018
DOI: 10.1021/acscombsci.8b00060
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Pot Parallel Synthesis of 3-Amino-1,2,4-triazoles

Abstract: A 1,2,4-triazole motif is present in numerous commercialized and investigational bioactive molecules. Despite its importance for medicinal chemistry, there is a lack of convenient combinatorial approaches toward this molecular core. Herein, we present a synthetic strategy suitable for the quick preparation of a library of structurally diverse 1,2,4-triazoles in a one-pot setting. The key steps include the formation of thioureas followed by S-alkylation using 1,3-propane sultone and consecutive ring closure lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Finally, the resulting S -alkylisothioureas 13 underwent cyclization with NaN 3 leading to the target products 8 , which were further purified by reverse-phase HPLC on the C 18 column. This reaction sequence can be considered as a modification of our previous method for the combinatorial synthesis of 3-amino-1,2,4-triazoles, where hydrazides were used as the nucleophilic reagents instead of NaN 3 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the resulting S -alkylisothioureas 13 underwent cyclization with NaN 3 leading to the target products 8 , which were further purified by reverse-phase HPLC on the C 18 column. This reaction sequence can be considered as a modification of our previous method for the combinatorial synthesis of 3-amino-1,2,4-triazoles, where hydrazides were used as the nucleophilic reagents instead of NaN 3 …”
Section: Resultsmentioning
confidence: 99%
“…We have suggested that the low efficiency of the first step (i.e., thiourea 12 preparation) in the isothiocyanate-based method might be a possible reason for its modest success rate. Recently, our group reported the efficient application of bis­(2,2,2-trifluoroethyl)­carbonate (BTC) and -thiocarbonate (BTTC) as reagents for preparation of unsymmetrical ureas , and thioureas, respectively. Therefore, a stepwise reaction of amines 15 and 11 with BTTC was envisaged for the preparation of 12 (BTTC-based method, Scheme A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Therefore, a vast number of functionalized 1,2,4triazoles have been accessed by means of annulation and cyclization reactions of various synthons and substrates. [1][2][3][4] Among these methods, aryldiazonium salts, [4][5][6][7] which are versatile and readily accessible 'NÀ N' synthons, have been utilized for the synthesis of 1,2,4-triazoles. [5] In 1970's, Masumoto disclosed the first synthesis of 1,3-disubstituted 1,2,4-triazoles via the base-promoted annulation of aryldiazonium salts with methyl isocyanoacetate, [5a] wherein only electronrich aryl groups could be harnessed to deliver methyl 1-aryl-1,2,4-triazole-3-carboxylates (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%